Integrasi Nalar Aqli dan Naqli dalam Pendidikan Islam Masa Abbasiyah: Relevansinya bagi Pendidikan Islam Kontemporer - Siti Rizqiyyah Fitriyani; Bilqis Awaliyyah Wahyudi; Faiz Fikri Al Fahmi; Nur Halimah; Aimi Farina Sariff (Tadabbur: Jurnal Integrasi Keilmuan, 2025)
The Abbasiyah period is frequently portrayed as the golden age of Islamic education, yet this label often separates political history, educational institutions, and intellectual traditions into independent narratives. This study examines how transmitted religious knowledge and rational-empirical inquiry were organized within the educational ecology of the Abbasid era and assesses their relevance to contemporary Islamic education. A qualitative historical literature approach was employed by comparing scholarly books, journal articles, and previous studies on Abbasid educational institutions, the translation movement, mosques, madrasas, and Bayt al-Hikmah. The findings show that the relationship between naqli and aqli reasoning did not emerge from a single centralized curriculum. It was produced through an institutional network comprising kuttab, mosque-based halaqah, libraries, book markets, hospitals, observatories, madrasas, and Bayt al-Hikmah, supported by patronage, waqf, scholarly mobility, and translation. Bayt al-Hikmah was an important intellectual infrastructure, but equating it directly with a modern university obscures its historically specific functions. The Abbasid experience remains relevant through its interdisciplinary orientation, literacy and research culture, institutional diversity, sustainable financing, and ethical commitment to knowledge. Its contemporary use, however, requires critical adaptation rather than romantic replication.